Pengaruh Kelangkaan Produk dengan Niat Beli Pelanggan - Nurfadilah Nurfadilah; Puspita Chairun Nisa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The purpose of this study is to explore the influence of limited-edition characteristics, perceived value, brand trust, Word of Mouth on the purchase intention of New Balance shoes. Findings from the limited-edition characteristics variable test were positively related to perceived value. Researchers also obtained the results that perceived value has a positive effect with brand trust. Researchers also obtained in the study that perceived value has a positive effect on purchase intention. Furthermore, researchers obtained the results Brand trust has a positive effect on purchase intention. And researchers obtained the results of Brand Trust having a positive effect with Word of Mouth (WOM). The population of this study are people who live in Jakarta and Bekasi. The sample in this study was 145 people. The most owned product is the New Balance Classic 574 Core. The sampling technique used purposive sampling method. The data analysis method used is path analysis through the Partial Least Squares Structural Equation Model (PLS-SEM). This research can be used for well-known brand companies to make their products limited so that they can increase sales.